Prescription patterns of traditional Chinese medications and potential consequences in patients with new-onset cardiac or vascular-related diseases: a nationwide cohort study - Sheng-Shing Lin; Hsin-Hui Tsai; Daniel Hsiang-Te Tsai; Chiu-Lin Tsai; Nanae Itokazu; Jaung-Geng Lin; Edward Chia-Cheng Lai; Hsiang-Wen Lin; Yu-Chang Hou (BMC Complementary Medicine and Therapies)
Abstract Background The patterns of Chinese medicine prescriptions, corresponding diagnoses, co-morbidities, and Western medication (WM) use among patients with cardiac or vascular-related diseases are uncertain. This research aimed to examine the patterns of Chinese medications (CMs, specifically in terms of extract granules), corresponding diagnoses, co-morbidities, and the use of WMs within specified follow-up periods among patients with potential of recurrent cardiac or vascular-related diseases and relevant outcomes. Methods We conducted a retrospective cohort study using Taiwan’s National Health Insurance Research Database. We enrolled patients with newly diagnosed cardiac or vascular-related diseases without cancer(s), transplantation, bleeding diagnoses, or catastrophic illness during the 2-year period prior to the corresponding diagnosis. Prior and non-prior CM users were matched based on their propensity scores. Finally, we compared the CM and WM patterns prescribed by physicians, and co-morbidities in the 6 months following the diagnosis and the secondary cardiac or vascular-related events in the 2 years following the diagnosis between the two groups using the standardized mean difference. Results Of 191,025 patients with newly diagnosed cardiac or vascular-related diseases, 39,341 (20.60%) were prescribed CMs. Moreover, after propensity score matching, we identified 39,168 prior CM users and 39,168 non-prior CM users. Regardless of prior CM use, both groups had a relatively high rate of comorbidities; CM or specific WM use; and incidence of severe cardiovascular, cerebrovascular, or thromboembolic events (33.81% vs. 31.97%) and severe bleeding (18.32% vs. 16.57%). Only CM exposure within 6 months after the index date differed significantly between the groups (73.51% vs. 30.34%). Conclusion We found that over 30% of patients with newly diagnosed cardiac or vascular disease initiated CM use, while 73.5% of prior CM users continued. This finding highlights the need for healthcare professionals to carefully assess the risk-to-benefit ratio of CM use alongside WMs for patients with cardiac or vascular-related diseases.